Bladder Cancer in an Inguinoscrotal Vesical Hernia. (18th October 2012) - Regis, Lucas; Lozano, Fernando; Planas, Jacques; Morote, Juan
Abstract : We present the case of a 79-year-old male who, due to hematuria, underwent cystoscopy that showed a lesion in the bladder dome. Transurethral resection was attempted, but access to the tumor by this route was impossible. Given the findings, a body CT scan was performed showing an inguinoscrotal hernia with vesical carcinoma contained. Open surgical treatment of the vesical carcinoma contained within the inguinoscrotal hernia was performed in conjunction with the hernia repair. The anatomical pathology report confirmed a high-grade urothelial carcinoma (stage pT2b) with a free resection margin of <1 mm. Adjuvant radiotherapy was selected for subsequent treatment. The presence of bladder tumor in an inguinoscrotal hernia is an uncommon finding and a diagnostic delay can be assumed. The initial therapeutic plan may need to be changed from the usual approaches due to the atypical presentation.